Combined endoscopic and microscopic transnasal approach for removal of large pituitary macroadenomas extending to paranasal sinuses - Bošnjak, Roman (Endoskopska revija, 2009)
Introduction. Removal of large pituitary macroadenomas with extrasellar extension to paranasal sinuses is a challenging field of skull base surgery that neccesiates cooperation between a neurosurgeon and arinologist. Combined endoscopic and microscopic transnasal approach extends the classic exposure via the transsphenoidal approach for intra-and suprasellar macroadenomas and gains added exposure of the parasellar, ethmoid and clival regions. Methods and Patients. Three patients with large nonsecretory intra-extracranial macroadenomas and panhypopituitarism were operated on by combined microscopic and endoscopic approach. In all cases intranasal, intraethmoid and intrasphenoid parts of macroadenoma were removed first by endoscopic techniquefollowed by microscopic technique of removal of the intrasellar, suprasellar and parasellar parts of the tumor. One patient had a previous transcranial surgery four years ago. Other two patients had tumors of similar large size, but underwent only one-staged transnasal surgery. Results. In all cases, the tumor was gross-totally removed from all extrasellar parts, except from parasellar space where incomplete removal was revealed by postoperative MRI scan. Visual symptoms were improved in all patients. Intraoperative CSF leak occured in one patient and was succesfully treated by lumbar drainage. She also had a mild transient diabetes insipidus. There were no additional neurological deficits and no rhinological problems.
Keywords: Adenoma; Pituitary Neoplasms; Surgery; Mikrokirurgija; Endoscopy; Hipofizne novotvorbe; Endoskopija; Microsurgery; Sfenoidna kost; Sphenoid Bone; Middle Age; Kavernozni sinus; Nasal Cavity; Srednja leta; Paranasal Sinus Neoplasms; Paranazalni sinus, novotvorbe; Nosna votlina; Cavernous Sinus; Adenom; novotvorbe; tumor; hipofiza; lobanjsko dno; endoskopska kirurgija